(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
This researchable paper aims to focus of the role & mechanism of market makers in Iraqi stock market through analyzing its role in other Arabian as well as global stock ones, especially in current period through activate the use of bonds, shares, and trying to create a continued price balance. Then decreasing the opportunity having gaps between highest and lowest level without reasonable causes. In addition trying to deactivate the common decision without supported information. Moreover, this paper aims to explain the rules of increasing liquidity and having balance to lead the market into positive direction. Thus, for achieving the above-mentioned requirements, such conditions should be underlined by market makers as well as the institute of stock market that has the ability to legislate then translate them into reality.